2019
DOI: 10.1158/2159-8290.cd-19-0289
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Colorectal Cancer–Associated APC Mutations Dictate Response to Tankyrase Inhibition

Abstract: The majority of colorectal cancers (CRCs) show hyperactivated WNT signaling due to inactivating mutations in the APC tumor suppressor. Genetically restoring Apc suppresses WNT and induces rapid and sustained tumor regression, implying that re-engaging this endogenous tumor suppressive mechanism may be an effective therapeutic strategy. Here, using new animal models, human cell lines, and ex vivo organoid cultures, we show that Tankyrase (TNKS) inhibition can control WNT hyperactivation and provide long-term tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 54 publications
3
71
0
Order By: Relevance
“…The blockade of TNKS enzymatic activity results in the accumulation of AXIN1/2-containing β-catenin degradosomes and reduced WNT/β-catenin signaling activity [18,19]. The development of TNKS inhibitors has received focus because of their potential as a possible anticancer treatment strategy, and chemical TNKS inhibition has been shown to impact a number of tumor models [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The blockade of TNKS enzymatic activity results in the accumulation of AXIN1/2-containing β-catenin degradosomes and reduced WNT/β-catenin signaling activity [18,19]. The development of TNKS inhibitors has received focus because of their potential as a possible anticancer treatment strategy, and chemical TNKS inhibition has been shown to impact a number of tumor models [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Yang and colleagues reported that Wnt/β-catenin signaling was involved in M2-like TAM polarization by regulating c-Myc, and knockdown of β-catenin in M2 TAMs suppressed the tumor-promoting functions of TAMs [39]. Although canonical Wnt/β-catenin signaling has been found to regulate M2-like TAM polarization, aberrant Wnt/β-catenin signaling in CRC, including aberrant APC and β-catenin, mainly occurs in cancer cells and affect the biological behaviors of tumor cells [40,41]. While aberrant noncanonical Wnt signaling pathway may be more likely to present in the tumor microenvironment of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that G4 ligands exert anticancer effects through telomeric and non-telomeric DNA damage induction and transcriptional/ translational perturbation of cancer-related genes | 3097 SEIMIYA in xenograft models. APC loss-of-function mutations are potential predictive biomarkers of tankyrase inhibitors, 56,57 whereas β-catenin/CTNNB1 gain-of-function mutations confer the drug resistance. 58 Because Wnt/β-catenin signaling works for intestinal epithelial cells, continuous administration of tankyrase inhibitors may cause intestinal toxicity.…”
Section: Apart From Human Trf1 Tankyrase-binding Proteins Includementioning
confidence: 99%